Identification of Risk and Protective Factors For Burnout Among Correctional Officers: A Systematic Literature Review - Mu’almar Hartatriana Sahesti; Dian Veronika Sakti Kaloeti (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The profession of correctional officers is classified as a high-stress occupation with significant task complexity. In addition to being responsible for the security of correctional facilities, officers are also tasked with the social rehabilitation of inmates under demanding, dynamic, and emotionally challenging working conditions. These multifaceted demands can lead to psychological fatigue and ultimately result in burnout, a chronic psychological condition characterized by emotional exhaustion, cynicism toward work, and reduced personal accomplishment. Burnout is shaped by the interaction of various risk and protective factors, stemming from both individual and organizational domains. This study employs a Systematic Literature Review (SLR) approach guided by the PRISMA framework. Articles were retrieved from major databases including Scopus, Science Direct, EBSCO, and SAGEpub using the following keywords: ("burnout" OR "emotional exhaustion" OR "cynicism" OR "depersonalization" OR "reduced personal accomplishment") AND ("correctional officers" OR "correctional staff" OR "prison staff" OR "prison officers")). Inclusion criteria comprised English- language articles published between 2015 and 2025, utilizing quantitative research designs, involving correctional officers as participants, and addressing risk or protective factors related to burnout. Analysis of the selected studies revealed that burnout among correctional officers is influenced by a range of individual and organizational factors. The most commonly reported risk factors include work– family conflict, insomnia, and prolonged occupational stress. Conversely, resilience and social support emerged as prominent protective factors. These findings emphasize that burnout among correctional officers is not solely the result of high work pressure, but also reflects the inadequacy of psychosocial resources within the work environment.